Self-Reported Low Self-Esteem. Intervention and Follow-Up in a Clinical Setting - Søren Ventegodt; Suzett Thegler; Tove Andreasen; Flemming Struve; Lars Enevoldsen; Laila Bassaine; Margrethe Torp; Joav Merrick (The Scientific World Journal)
At the Research Clinic for Holistic Medicine in Copenhagen, 43 patients who presented with low or very low self-esteem were treated with psychodynamic short-term therapy complemented with bodywork. They received an average of 20 sessions at a cost of 1,600 EURO. The bodywork helped the patients to confront old emotional pain from childhood trauma repressed to the body-mind. Results showed that 60.5% recovered from low selfesteem (95% CI: 44.41–75.02%). Calculated from this, we have NNT = 1.33–2.25. Almost all aspects of life improved at the same time (p < 0.01): physical health, mental health, quality of life, and ability to function in a number of important areas (partner, friends, sexually, and socially). This indicated that we had successfully induced existential healing (Antonovsky salutogenesis). The strategy of improving self-esteem can be the key to a new life for patients presenting with low quality of life, poor health (physical and/omental), and poor ability to function. The patients were strongly motivated and willing to endure strong emotional pain provoked by the therapy. The rate of recovery is comparable to the most successful interventions with psychological and psychiatric treatment. Clinical holistic treatment has many advantages: efficiency, low cost, lack of negative side effects, lasting results, lack of use of psychopharmacological drugs (often with side effects), and an important preventive dimension.